Sports facilities, socio-economic context and overweight among the childhood population in two southern European cities: a cross sectional study - Romana Albaladejo; Rosa Villanueva; Paloma Astasio; Paloma Ortega; Juana Santos; Enrique Regidor (BMC, 2019)
Abstract Background To evaluate relationship between socio-economic environment and overweight in Madrid and Barcelona, adjusting for possible confounding factors. Methods We obtained three indicators which reflected socio-economic context, namely, unemployment rate, percentage of population with tertiary education, and percentage with a second home. The design is a cross sectional study. The association with overweight was estimated using odds ratios by multilevel logistic regression. The statistical analysis, data synthesis, or model creation was performed from the 2017. In all, 707 children from 21 districts of Madrid and 474 children from 10 districts of Barcelona were analysed. Results In Madrid, standardised ORs for personal and family characteristics were 1.17, 1.53 and 1.57 by reference to unemployment rate and percentages of population with a university education and second home. After adjustment, only the OR obtained with unemployment rate decreased, specifically by 58%. In Barcelona, the following ORs were obtained: 1.80 with unemployment rate; 1.80 with population having a university education; and 1.86 with population having a second home. After being standardised, these ORs decreased by 14% in the case of unemployment rate, 10% in the case of population with a university education, and 9% in the case of population with a second home. Conclusions Overweight displayed a risk gradient in Madrid and Barcelona alike. This risk of overweight is not accounted for by physical inactivity and could, in part, be due to the availability of sports facilities.